2012
DOI: 10.1364/ao.51.004275
|View full text |Cite
|
Sign up to set email alerts
|

Optimal wavelength band clustering for multispectral iris recognition

Abstract: This work explores the possibility of clustering spectral wavelengths based on the maximum dissimilarity of iris textures. The eventual goal is to determine how many bands of spectral wavelengths will be enough for iris multispectral fusion and to find these bands that will provide higher performance of iris multispectral recognition. A multispectral acquisition system was first designed for imaging the iris at narrow spectral bands in the range of 420 to 940 nm. Next, a set of 60 human iris images that corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…al. [39] similarly found that accuracy could be improved by combining scores acquired at various illumination wavelengths. Most of the improvement in their analysis occurred when they combined scores acquired at 700 and 850 nm within the NIR band.…”
Section: Score Levelmentioning
confidence: 94%
“…al. [39] similarly found that accuracy could be improved by combining scores acquired at various illumination wavelengths. Most of the improvement in their analysis occurred when they combined scores acquired at 700 and 850 nm within the NIR band.…”
Section: Score Levelmentioning
confidence: 94%
“…Tan et al utilized ordinal measures, color analysis, texture representation, and semantic information as iris features as well as the weighted sum rule to generate the fused score for classification [15]. Gong et al selected three wavelength bands to represent an iris and then integrated them using agglomerative clustering based on a two-dimensional principal component analysis [16]. The fusion of multiple features is regarded as a positive step towards the development of extremely ambitious types of iris recognition [17].…”
Section: Introductionmentioning
confidence: 99%